Comparative analysis of transmissions of mine diesel locomotives with different component schemes - Samorodov, V. B.; Taran, I. O.; Bondarenko, A. I.; Klymenko, I. Yu. (Національний гірничий університет, 2019)
Purpose. To develop mathematical models and techniques to model stepless transmissions operating as a part of a diesel locomotive, to improve reliability of the results of diesel locomotive movement under actual operating conditions. Methodology. Values of kinematic parameters, power parameters, and energy parameters are identified with the help of solving a system of algebraic equations by Simulink subsystem of Matlab system. Integrated study of changes in basic transmission parameters of "input differential" and "output differential" in terms of its operation within both transport and traction ranges is necessary to determine the initial data to model braking process of a mine diesel locomotive. Findings. The paper has performed comparative analysis of "input differential" and "output differential" hydrostatic mechanical transmissions (HMTs) by means of integrated study of changes in power parameters, kinematic parameters, and energy parameters of the transmissions in terms of traction and transport ranges of motion of a mine diesel locomotive. Values of these parameters are determined by means of solving the system of algebraic equations being considered as the development of a set of mathematical models and techniques to model stepless transmissions operating as a part of a mine diesel locomotive. Originality. The obtained results of integrated study of changes in power, kinematic and energy parameters of "input differential" and "output differential" HMTs in terms of their operation within both transport and traction ranges indicate that each transmission has its own strengths and weaknesses. That is why the both HMTs will be used in future while analyzing a braking process of a mine diesel locomotive. Practical value. The developed structural transmission scheme, mathematical model explaining changes in kinematic parameters and power ones, determined kinematic, power parameters and efficiency of hydrostatic drive in future can be applied as the initial data to model a braking process of a mine diesel locomotive.

Мета. Розробка комплексу математичних моделей і методик моделювання безступінчастих трансмісій, що працюють у складі дизелевоза, для підвищення достовірності результатів аналізу руху дизелевоза в реальних умовах експлуатації. Методика. Значення кінематичних, силових і енергетичних параметрів визначаються шляхом розв'язання системи алгебраїчних рівнянь з використанням підсистеми Simulink системи Matlab. Комплексне дослідження зміни основних параметрів трансмісій "з диференціалом на вході" та "з диференціалом на виході" при їх роботі на транспортному й тяговому діапазонах необхідно для визначення вихідних даних для моделювання процесу гальмування шахтного дизелевоза. Результати. У роботі виконано порівняльний аналіз гідрооб'ємно-механічних трансмісій (ГОМТ) "з диференціалом на вході" та "з диференціалом на виході" шляхом комплексного дослідження зміни силових, кінематичних і енергетичних параметрів трансмісій при роботі на тяговому та транспортному діапазонах руху шахтного дизелевоза. Значення цих параметрів визначені шляхом розв'язання складеної системи алгебраїчних рівнянь, що розцінюється як розвиток комплексу математичних моделей і методик моделювання безступінчастих трансмісій, що працюють у складі дизелевоза. Наукова новизна. Отримані результати комплексного дослідження зміни силових, кінематичних і енергетичних параметрів ГОМТ "з диференціалом на вході" та "з диференціалом на виході" при роботі на транспортному й тяговому діапазонах свідчать про те, що кожна трансмісія має свої переваги й недоліки. Саме тому обидві ГОМТ будуть використовуватися в подальшому при дослідженні процесу гальмування шахтних дизелевозів. Практична значимість. Розроблена структурна схема трансмісії, математична модель, що описує зміну кінематичних і силових параметрів, а також обчислені кінематичні, силові параметри та ККД гідрооб’ємної передачі в подальшому можуть буди використані як вихідні дані для моделювання процесу гальмування шахтного дизелевоза.
Порівняльний аналіз трансмісій шахтних дизелевозів з різними компонувальними схемами
Keywords: hydrostatic mechanical transmissions; braking process; mathematical model; hydrostatic drive; гідрооб'ємно-механічна трансмісія; диференціал; процес гальмування; математична модель